2017
DOI: 10.1158/1078-0432.ccr-16-1930
|View full text |Cite
|
Sign up to set email alerts
|

Axl Blockade by BGB324 Inhibits BCR-ABL Tyrosine Kinase Inhibitor–Sensitive and -Resistant Chronic Myeloid Leukemia

Abstract: Ben Batalla, I. et al. (2017) Axl blockade by BGB324 inhibits BCR-ABL tyrosine kinase inhibitor-sensitive and -resistant chronic myeloid leukemia. Clinical Cancer Research, 23(9), pp. 2289-2300. (doi:10.1158/1078-0432.CCR-16-1930 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/131767/ STATEMENT OF TRANSLATIONAL RELEVANCEABL tyrosine kinas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…Indeed, small molecule inhibitors (such as BGB324, ONO-747, TP-0903, MGCD516, and BPI-9016M) or specific antibodies (CAB-AXL-ADC) that target the AXL receptor or the AXL pathway are currently under clinical evaluation in 14 clinical trials as a monotherapy or in combination with other therapies in different settings (ClinicalTrials.gov). The clinical outcomes of these studies are not yet available, but preclinical models indicate that the efficacy of a single agent targeting AXL signaling can be limited by the upregulation of other receptors, such as MERTK (41), while the potency of several combination therapies is superior to that of the monotherapies (15,40,(42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, small molecule inhibitors (such as BGB324, ONO-747, TP-0903, MGCD516, and BPI-9016M) or specific antibodies (CAB-AXL-ADC) that target the AXL receptor or the AXL pathway are currently under clinical evaluation in 14 clinical trials as a monotherapy or in combination with other therapies in different settings (ClinicalTrials.gov). The clinical outcomes of these studies are not yet available, but preclinical models indicate that the efficacy of a single agent targeting AXL signaling can be limited by the upregulation of other receptors, such as MERTK (41), while the potency of several combination therapies is superior to that of the monotherapies (15,40,(42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…A recent example is from a study that showed Axl to be upregulated in CML patients that had developed resistance to BCR-Abl small-molecule inhibition, including through a T315I mutation in BCR-Abl. The selective Axl small-molecule inhibitor BGB324 inhibited the resistant CML cells independent of BCR-Abl mutational status (33). This example indicates an efficacious employment of Axl inhibition at the earliest signs of resistance development to first-line or targeted therapies.…”
Section: Tam Inhibition To Treat Tumor Drug Resistancementioning
confidence: 83%
“…The efficacy of bemcentinib in combination with chemotherapy is being tested currently in pancreatic cancer patients (NCT03649321). Pharmacological inhibition of AXL has also been shown to decrease metastasis in breast cancer models (19,41) and improve the efficacy of doxorubicin, BCR-ABL inhibitor, docetaxel, paclitaxel, EGFR inhibitor and nivolumab in breast cancer, chronic myelogenous leukemia, prostate cancer, uterine serous cancer, NSCLC and glioblastoma models, respectively (11,19,(42)(43)(44)(45). (46,47).…”
Section: Discussionmentioning
confidence: 99%